La moral en acción. Teoría y práctica durante el porfiriato - Briseño Senosiain, Lillian (El Colegio de México, A.C., 2005)
During the nineteenth century, civil and ecclesiastical authorities made important efforts to implant  in the population moral values in tune with the liberal and conservative ideas of the groups in power.  During  the Porfiriato, in a country in which secularization and positivist ideas gained ground, the liberal State maintained  its intention of the “moral creation”  of the new Mexicans it required.  Despite  all these  efforts,  the  values that were transmitted did not  manage to alter some habits strongly enrooted among  a society  apparently  assuming  the  “worldly” and “divine” risks of its behavior. By studying  proclaimed moral values and opposing  them to daily practices, the author  reveals the lack of correspondence between them, which leads us to dispute the effectiveness of these moral policies.